2012
DOI: 10.1302/0301-620x.94b5.27073
|View full text |Cite
|
Sign up to set email alerts
|

A financial analysis of revision hip arthroplasty

Abstract: Revision arthroplasty of the hip is expensive owing to the increased cost of pre-operative investigations, surgical implants and instrumentation, protracted hospital stay and drugs. We compared the costs of performing this surgery for aseptic loosening, dislocation, deep infection and peri-prosthetic fracture. Clinical, demographic and economic data were obtained for 305 consecutive revision total hip replacements in 286 patients performed at a tertiary referral centre between 1999 and 2008. The mean total cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(100 citation statements)
references
References 27 publications
0
99
0
1
Order By: Relevance
“…The cost of a single revision surgery for PJI is higher than the cost of revision for noninfectious reasons, with postulated reasons including prolonged procedure duration, increased blood loss, increased use of bone allograft, and increased complications (14). More complicated treatment strategies involving multiple individual surgeries further increase this cost compared to the cost of only a single surgery.…”
Section: Economic Impactmentioning
confidence: 99%
“…The cost of a single revision surgery for PJI is higher than the cost of revision for noninfectious reasons, with postulated reasons including prolonged procedure duration, increased blood loss, increased use of bone allograft, and increased complications (14). More complicated treatment strategies involving multiple individual surgeries further increase this cost compared to the cost of only a single surgery.…”
Section: Economic Impactmentioning
confidence: 99%
“…Orthopaedic SSI has been reported to increase the mortality risk by 50% and the hospital stay by, on average, 11.5-14 days and to double the rehospitalisation rates. 4,5,39 A UK study by Vanhegan et al 40 compared the costs of revision operations for aseptic loosening, dislocation, deep infection and periprosthetic fracture. Clinical, demographic and economic data were collected for 305 consecutive-revision THRs in 286 patients in a single tertiary referral unit.…”
Section: Permanent Resectionmentioning
confidence: 99%
“…41 They found that in their institution, the average hospital stay was 7.5 days for primary THA and 30.6 days for revisions because of infection. Vanhegan et al 40 compared the costs of revision operations for aseptic loosening, dislocation, deep infection and periprosthetic fracture. Clinical, demographic and economic data were collected for 305 consecutive revision THRs in 286 patients in a single tertiary referral unit.…”
Section: Background and Study Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although orthopedic deviceassociated infections (ODAI) are uncommon, occurring in only 1 to 2% of patients with hip and knee replacements and up to 6% of patients after internal fixation of closed fractures, their management is difficult (1). Management can require multiple revision surgeries and prolonged antibiotic treatment, may result in permanent disabilities, and is associated with high costs (2,3).…”
mentioning
confidence: 99%